(untitled) (Biological Sciences - PJSIR, 1995)
Transition metal complexes of Mnf ll), Co(ll) and Ni(II) ions with 2-hydroxyphenylthiourea. 2-carboxyphenylthiourea and 4-methyl-phenylthiourea have been synthesized and characterized on the basis of el- emental analyses. conductivity and magnetic measurements and from their IR spectral studies. The complexes have thegeneral formula: Kz[Mz(U-)2 (NO)zl. U = Dinegativedeprotonatedformofthe ligand.2;hydroxyphenylthiourea; [M(L)zNO,l. where L= 4-methylphenylthiourea and [Mz(L’NNO,)2]’ where L-= Urn-negativedeprotonated formof the ligand.2-carboxyphenylthiourea.with2-hydroxyphenylthioureaand2-carboxyphenylthiourea. MnOI).Co(ll) and Ni(JI)metal ions form 5-coordinate bridging complexes whereas4-methylphenylthiourea gives rise to 4-coordinated complexes with the same metal ions. The antibacterial activity of the ligands and their complexes have been tested with Bacillus subtilis. Somecomplexes show higheractivity thenthat of the free ligand value whereas in some cases the activity decreases. Some complexes were foundto retainthe same activity as that of the ligand.